The Submarine Boundaries of Mount Etna’s Unstable Southeastern Flank - Urlaub, Morelia; Geersen, Jacob; Petersen, Florian; Gross, Felix; Bonforte, Alessandro; Krastel, Sebastian; Kopp, Heidrun (Frontiers in Earth Science, 2022)
Coastal and ocean island volcanoes are renowned for having unstable flanks, which expresses as slow seawards flank sliding observable by geodetic techniques and/or catastrophic sector collapses. A large section of these unstable flanks is often below sea level, where information on the volcanotectonic structure and ground deformation are limited. Consequently, kinematic models that attempt to explain measured ground deformation onshore associated to flank instability are poorly constrained in the offshore area. Here we attempt to determine the locations and the morphotectonic structures of the boundaries of the submerged unstable southeastern flank of Mount Etna (Italy). The integration of new and published marine hydroacoustic and seismic data, seafloor geodetic time series, and seismological information allows identifying the southern lateral boundary with a high level of confidence. For the northern and the distal (seaward) boundaries, we discuss possible hypotheses regarding their locations based on seismic and bathymetric analyses. The information on the submarine boundaries of the moving flank may now inform kinematic models. Our results demonstrate that microbathymetric surveys and seafloor geodetic observations are key data sets to decipher complex submerged volcanotectonic settings as found at most coastal and ocean island volcanoes.